Geospatial mapping of biomass supply and demand for household energy management in Nepal. (2021) - Adhikari, N.P.; Adhikari, R.C.
Abstract: This paper presents a geospatial mapping model for assessing spatial distribution and demand of biomass sources for household energy use in Nepal. In the context of rural households, correlation between supply and demand of biomass is crucial for designing effective rural energy programs. Three districts were considered to represent the country's main topographical regions: lowlands, hills, and mountains, where geospatial distribution and demand of biomass are different. The supply potential of fuelwood was assessed using Geographical Information System (GIS) tool, and the potential of crop residues and dung and household energy demands were determined by field surveys and experiments. The results showed that households with secure access to biomass sources in lowlands, hills and mountains were 57%, 50% and 3% respectively. In lowlands, crop residues and dung were extensively used due to lack of forest biomass, whereas forest biomass was extensively used in hills and mountains, with negligible use of crop residues and animal dung. The results indicate that use of improved cooking stoves and biogas was negligible and thus cleaner biomass energy conversion and cooking technologies are needed to achieve universal target of clean cooking for all. The GIS model provided better estimation of biomass energy supply potential in the communities, which is crucial in the design of energy policies for sustainable clean cooking solutions. It is anticipated that this geospatial mapping model is also applicable to the cases of other developing countries, which have dominant biomass consumption for household energy use. Highlights: A geospatial mapping model using GIS for assessing spatial distribution of biomass sources is presented. Geospatial distributions of fuelwood, crop residues, and animal dung in Nepal have been assessed. The potential of crop residues and dung and household energy demands were determined by field surveys and experiments. The uses of improved cooking stoves and biogas were negligible in the rural households of Nepal. Cleaner biomass energy conversion and cooking technologies are needed to achieve universal target of clean cooking for all.